Comparison of gene targets and sampling regimes for SARS-CoV-2 quantification for wastewater epidemiology in UK prisons - Kelly Jobling; Marcos Quintela-Baluja; Francis Hassard; Panagiota Adamou; Adrian Blackburn; Term Research Team; Shannon McIntyre-Nolan; Oscar O'Mara; Jesus L. Romalde; Mariachiara Di Cesare; David W. Graham (IWA Publishing, 2024)
Prisons are high-risk settings for infectious disease transmission, due to their enclosed and semi-enclosed environments. The proximity between prisoners and staff, and the diversity of prisons reduces the effectiveness of non-pharmaceutical interventions, such as social distancing. Therefore, alternative health monitoring methods, such as wastewater-based epidemiology (WBE), are needed to track pathogens, including SARS-CoV-2. This pilot study assessed WBE to quantify SARS-CoV-2 prevalence in prison wastewater to determine its utility within a health protection system for residents. The study analysed 266 samples from six prisons in England over a 12-week period for nucleoprotein 1 (N1 gene) and envelope protein (E gene) using quantitative reverse transcriptase-polymerase chain reaction. Both gene assays successfully detected SARS-CoV-2 fragments in wastewater samples, with both genes significantly correlating with COVID-19 case numbers across the prisons (p < 0.01). However, in 25% of the SARS-positive samples, only one gene target was detected, suggesting that both genes be used to reduce false-negative results. No significant differences were observed between 14- and 2-h composite samples, although 2-h samples showed greater signal variance. Population normalisation did not improve correlations between the N1 and E genes and COVID-19 case data. Overall, WBE shows considerable promise for health protection in prison settings. HIGHLIGHTS Wastewater epidemiology is effective in flagging COVID-19 cases in prison settings.; SARS-CoV-2 levels were quantified using N1 and E gene targets.; Both targets should be used in routine analysis to reduce false negatives.; COVID-19 case numbers significantly correlated with both wastewater gene targets across all samples.; Each prison is different - local activities are important when designing sampling programmes.;